The Holy Months Impact of Islam Toward Stock Price in Jakarta Islamic Index (JII) - Yusri Rahma Yanti; Guntur Kusuma Wardana; Rini Safitri (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2021)
The purpose of this research is to determine the effect of anomaly calendar towards stock price in haram months (Muharam, Rajab, Zulkaidah, and Zulhijjah) in Jakarta Islamic Index (JII). Population for this research include all stockmarkets under the category of Jakarta Islamic Index (JII) during the period of 1436H–1440H. Samples were chosen using purposive sampling, which include 44 companies. Results showed that there are no difference in JII stock price during holy months of Rajab, Zulkaidah, and Zulhijjah compared to any other period of the same year. This finding means that muslim society in Indonesia did not create an out of ordinary transaction in the market and there will be no significant change during the period of holy months. However, in Muharram, results showed different outcome compared to the other holy months.